Prenatal Ultrasonographic Diagnosis of Cataract: In Utero Manifestations of Cryptic Disease - Ashwal, Eran; Achiron, Asaf; Gilboa, Yinon; Berkenstadt, Michal; Rosner, Mordecai; Achiron, Reuven (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Purpose To report and review our experience with antenatal evaluation for fetuses diagnosed with congenital cataract.Materials and Methods We retrospectively identified pregnancies diagnosed with fetal cataract during antenatal ultrasound. Evaluation of fetal eyes included intraocular anatomy and biometry. Data on fetal malformations, serology and fetal karyotype were collected.Results 8 cases, identified over the course of 10 years, were reviewed. Week 15 was the mean time for diagnosis (range 11 – 34). Extraocular anomalies were demonstrated in 6 cases (central nervous system, cardiac and renal systems). Additional intraocular abnormalities were detected in two cases: one fetus had persistent hyperplastic primary vitreous and another had bilateral retinal detachment. All cases but one involved cataracts in both eyes. The unilateral case was associated with microphthalmic aphakia. All cases had negative serology for TORCHs. 7 out of the 8 fetuses were terminated. The only one who survived developed in utero cataracts secondary to maternal steroid therapy. He underwent bilateral cataract extraction during the first weeks of life and ophthalmologic evaluation at 2 years of age was unremarkable, without any visual impairment.Conclusion In most cases, fetal cataract was associated with additional abnormalities, both intra- and extra-ocular. In instances when cataracts are isolated, we suggest conducting a detailed and thorough in utero ophthalmic examination in order to improve antenatal parental counselling.
Keywords: fetal cataract; ultrasound diagnosis; prenatal counseling